Unsteady heat transfer properties of spray falling over a horizontal tube in an oily sewage source heat pump. (October 2020) - Mao, Ning; Hao, Jingyu; He, Tianbiao; Xu, Yingjie; Song, Mengjie; Tang, Jianfeng
Highlights: Spray falling film of oily wastewater over a horizontal tube was investigated. VOF model was used to simulate the gas-liquid falling film flow. The unsteady film and tube temperature distributions were analyzed. The unsteady heat transfer properties were investigated. The effects of oil content, spray density and tube diameter were studied. Abstract: The oil exploit in late-period oilfield usually produce large amount of oily wastewater at moderate and high temperature, the thermal energy of which can be recuperated through a sewage source heat pump (SSHP). Among different kinds of heat recovery facility in SSHP, the spray heat exchanger is a better choice to recover energy from the oily wastewater due to its advantages of simple structure, high heat transfer efficiency and anti-blocking ability. However, the spray falling heat transfer was an unsteady procedure, and the complex properties of oil-water mixer will lead to different heat transfer and flow characteristics in the heat exchanger, which also affect the unsteady heat transfer. Hence, in this paper, a numerical model with VOF method was established to study the unsteady heat transfer properties of oily wastewater spray falling film on a horizontal tube, and the effects of different oil contents, spray densities and tube diameters on the unsteady properties of heat transfer coefficient. The results show that the film temperature and tube temperature were continuously varying with time, and the slight variation in upper part and greater variation in lower part of the tube were observed. A further understanding on the flow field of liquid on the tube revealed the unsteady heat transfer was due to the falling flow instability. Thereafter, the influences of oil content, tube diameter and spray density on the unsteady heat transfer were analyzed. It was found that the decrease in oil content, increase in tube diameter will reduce the fluctuation intensity of heat transfer properties.